Determinants of Contract Choice: The Use of Warrants to Compensate Underwriters of Seasoned Equity Issues - NG, CHEE K.; SMITH, RICHARD L. (Journal of Finance, 1996)
ABSTRACT The issuer's decision to include warrants as compensation to underwriters is studied for a sample of 1,991 negotiated firm commitment issues of seasoned equity. Using a two‐stage logit model to correct for self‐selection bias, we find direct evidence that warrant compensation functions as a bond, substituting for reputational capital and enabling the underwriter to certify the issue price. To a lesser degree, the decision also is affected by regulations on underwriter compensation and on the use of underwriter warrants. Issuers' decisions are consistent with an objective of minimizing total underwriting cost, including cash compensation, warrants, and underpricing.